2010
DOI: 10.1039/b923556f
|View full text |Cite
|
Sign up to set email alerts
|

Oligoproline helices as structurally defined scaffolds for oligomeric G protein-coupled receptor ligands

Abstract: Oligoprolines (OPs) are used as rigid backbone scaffolds for the design of oligomeric ligands that target specific G protein-coupled receptors. The OPs were designed to vary in length, the position and number of the ligand-functionalized residues incorporated. For all synthesized compounds a typical PP type II helix was evidenced by circular dichroism indicating that decoration of the helix with large ligands did not affect the helical conformation. Pharmacological evaluation revealed that oligomerization of a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
21
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(21 citation statements)
references
References 29 publications
0
21
0
Order By: Relevance
“…Oligoprolines, which are amongst the most rigid peptides, have become increasingly popular in recent years as “molecular rulers” and “molecular scaffolds” 1. They have been used for energy transfer,2–8 distance measurements in biomolecules,9, 10 tumor targeting,11, 12 electron‐transfer studies,13, 14 the development of protein– protein interaction inhibitors,15 hierarchical supramolecular assemblies,16 and for the size‐controlled formation of metal nanoparticles 17. Thus, detailed knowledge of the dimensions and conformational rigidity of oligoprolines is highly sought after.…”
Section: Introductionmentioning
confidence: 99%
“…Oligoprolines, which are amongst the most rigid peptides, have become increasingly popular in recent years as “molecular rulers” and “molecular scaffolds” 1. They have been used for energy transfer,2–8 distance measurements in biomolecules,9, 10 tumor targeting,11, 12 electron‐transfer studies,13, 14 the development of protein– protein interaction inhibitors,15 hierarchical supramolecular assemblies,16 and for the size‐controlled formation of metal nanoparticles 17. Thus, detailed knowledge of the dimensions and conformational rigidity of oligoprolines is highly sought after.…”
Section: Introductionmentioning
confidence: 99%
“…17o, p, 32c, 59 In general, the azidoacetate reacted more rapidly than the azidoproline, likely due to reduced steric restriction, though both were effective in azide-alkyne coupling reactions.…”
Section: Resultsmentioning
confidence: 99%
“…It was suggested that a spacer length of 20–24 atoms was ideal when directed in a specific orientation to allow for binding of the two pharmacophores at the respective receptors 35. The variety of spacer groups are presented in Table 2, accompanied by additional examples including some of the vast array of spacers synthesised by Bonger et al 6971. who generated bivalent ligands targeting the gonadotropin releasing hormone receptor (GnRHR) with rigid benzene‐based scaffolds ( 21 , 23 , 26 ) 70…”
Section: General Features Of Bivalent Ligandsmentioning
confidence: 99%
“…It is interesting to note the use of polybutylene glycol spacer groups,73 which have been designed to counter the natural coil‐like conformation obtained when using PEG spacers,7476 whilst retaining an element of hydrophilicity and flexibility. On the other hand, multiple oligoproline residues ( 24 ) have been used to form well‐defined helical structures77 for the synthesis of specifically oriented bivalent ligands with a coiled spacer 69. Another alternative to improving the hydrophilicity of the bivalent ligand (Table 2) is the incorporation of piperazine into the spacer group ( 28 ), which has slightly less flexibility than an alkyl chain and PEG spacer, but slightly more than polyamide chains, and for this reason it is an important design consideration for bivalent ligands.…”
Section: General Features Of Bivalent Ligandsmentioning
confidence: 99%